Primary lower segment caesarean section in multipara: materno-fetal outcomes - Agrawal, Grishma P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: All-natural birth has a purpose and a plan; who would think of tearing open the chrysalis as the butterfly is emerging? Who would break the shell to pull the chick out?” ~ Marie Mongon. It is of particular interest, in light of increased incidence of abdominal delivery throughout the country and in the world, to judge the validity of this procedure when used for the first time in the multipara. Methods: All the cases of Primary caesarean delivery in multipara over a period of 18 months were studied with regards to the indication, associated risks factors, and perinatal morbidity and mortality. The primary objective of the study was to find out the status of primary Lower Segment Caesarean Section (LSCS) in multipara in tertiary care center. Results: The overall incidence of LSCS was 30.7%. The incidence of Primary LSCS in multipara was 23.4%. The most common indication of LSCS was Foetal Distress i.e. 40.8%. Almost all caesarean sections were done in Emergency (99.2%). 12.3% of patients underwent PPH intra-operatively with 0.7% patient requiring Obstetric hysterectomy. Majority of the neonates were admitted in NICU for Respiratory Distress (30%). Major cause of Post-operative morbidity was wound gape seen in 10.8% patients. Conclusions: The fact that a multipara has had one or more vaginal deliveries should be regarded as an optimistic historical fact, not as diagnostic criteria for spontaneous delivery of the pregnancy at hand. Hence a multiparous woman in labour requires the same attention as that of primigravida and may still require a caesarean section for safe delivery. Good antenatal and intrapartum care and early referral will help reduce the maternal and perinatal morbidity.